Pilot study on cultural and metagenomic analysis of bile and biliary stentslead to unveiling the key players in stent occlusion - Cacaci, Margherita; De Maio, Flavio; Matteo, Maria Valeria; Posteraro, Brunella; Di Vito, Maura; Menchinelli, Giulia; Tringali, Andrea; Monzo, Francesca Romana; Torelli, Riccardo; Costamagna, Guido; Spada, Cristiano; Bugli, Francesca; et al. (Scientific reports, 2024)
Endoscopic Retrograde Cholangio-Pancreatography (ERCP) with biliary stenting is a minimally invasive medical procedure employed to address both malignant and benign obstructions within the biliary tract. Benign biliary strictures (BBSs), typically arising from surgical interventions such as liver transplants and cholecystectomy, as well as chronic inflammatory conditions, present a common clinical challenge. The current gold standard for treating BBSs involves the periodic insertion of plastic stents at intervals of 3–4 months, spanning a course of approximately one year. Unfortunately, stent occlusion emerges as a prevalent issue within this treatment paradigm, leading to the recurrence of symptoms and necessitating repeated ERCPs. In response to this clinical concern, we initiated a pilot study, delving into the microbial composition present in bile and on the inner surfaces of plastic stents. This investigation encompassed 22 patients afflicted by BBSs who had previously undergone ERCP with plastic stent placement. Our preliminary findings offered promising insights into the microbial culprits behind stent occlusion, with Enterobacter and Lactobacillus spp. standing out as prominent bacterial species known for their biofilm-forming tendencies on stent surfaces. These revelations hold promise for potential interventions, including targeted antimicrobial therapies aimed at curtailing bacterial growth on stents and the development of advanced stent materials boasting anti-biofilm properties.